Personal income tax reform: consensus, outliers, specifics and some sensitive issues - Pope, Jeffrey (Renee McDonald, 2007)
The case for significant Australian Personal Tax ("PIT") reform is overwhelming, as argued by (at least) eleven substantive business, professional and academic research reports and papers in the past few years, including work by this author. Essentially there is broad consensus for company and PIT rate alignment (or equalisation) at 30 per cent and associated simplificatio measures. Although strongly argued by this author and several other academics, there is generally little support for a substanitally increased tax-free threshold. in a revenue neutral analysis, this author has earlier suggested that significant PIT reform necessitates a higher Goods and Services Tax ("GST") rate of 15 per cent. Both proposals are outliers. This paper builds upon this analysis and emphasises the key factors that significant PIT reform would entail, such as the abolition of Work-Related Expenses, other deductions and offsets, the introduction of withholding taxes and much greater use of technological solutions. The final part of the paper considers several sensitive issues that need to be considered before undertaking significant PIT reform, including negative gearing and inter-generational distribution. The auther concludes by emphasising the key issues and challenges facing this complex Australian PIT reform debate, including the importance of substanitally reducing the number of PIT filers.